Cardiologists' attitudes on communication about prognosis with heart failure patients - Martje H.L. van derWal; Lisa Hjelmfors; Anna Strömberg; Tiny Jaarsma (ESC Heart Failure)
Abstract Aim According to guidelines, a prognosis should be discussed with all heart failure (HF) patients. However, many patients do not have these conversations with a healthcare provider. The aim of this study was to describe attitudes of cardiologists in Sweden and the Netherlands regarding this topic. Methods and results A survey was sent to 250 cardiologists in Sweden and the Netherlands with questions whether should the prognosis be discussed, what time should the prognosis be discussed, whom should discuss, what barriers were experienced and how difficult it is to discuss the prognosis (scale from 1–10). A total of 88 cardiologists participated in the study. Most cardiologists (82%) reported to discussing the prognosis with all HF patients; 47% at the time of diagnoses. The patient's own cardiologist, another cardiologist, the HF nurse, or the general practitioner could discuss this with the patient. Important barriers were cognitive problems (69%) and a lack of time (64%). Cardiologists found it not very difficult to discuss the topic (mean score 4.2) with a significant difference between Swedish and Dutch cardiologist (4.7 vs. 3.7; P < 0.05). Conclusion Most cardiologists found it important to discuss the prognosis with HF patients although there are several barriers. Swedish cardiologists found it more difficult compared with their Dutch colleagues. A multidisciplinary approach seems important for improvement of discussing prognosis with HF patients.